2016
DOI: 10.1108/jeee-09-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Predicting entrepreneurial intentions of freshmen students from EAO modeling and personal background

Abstract: Purpose The purpose of this paper is to study the effects of personal background and entrepreneurial attitudes on entrepreneurial intentions of Saudi Freshmen students of Al Imam Mohammad Ibn Saud Islamic University. After reviewing the literature and related theories on entrepreneurship, attitudes and intentions, this study provides a conceptual framework trying to identify the effects of most influential factors on individual’s intention to become an entrepreneur. Design/methodology/approach Through a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 55 publications
1
18
1
Order By: Relevance
“…National Transformation Plan 2020 and Saudi Vision 2030 ) of a country that faces daunting challenges (e.g. booming of the young population and increase in the unemployment rate among others) (Aloulou, 2016a, 2016b; McKinsey and Company, 2015; Porter, 2012; Saudi Council of Economic and Development Affairs, 2016; World Bank Group, 2018). The country must embrace significant change to its economic growth model to create more jobs for its young, educated citizens (Aloulou, 2017; McKinsey and Company, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…National Transformation Plan 2020 and Saudi Vision 2030 ) of a country that faces daunting challenges (e.g. booming of the young population and increase in the unemployment rate among others) (Aloulou, 2016a, 2016b; McKinsey and Company, 2015; Porter, 2012; Saudi Council of Economic and Development Affairs, 2016; World Bank Group, 2018). The country must embrace significant change to its economic growth model to create more jobs for its young, educated citizens (Aloulou, 2017; McKinsey and Company, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the researchers who applied the Shapero and Sokol's (1982) entrepreneurial event model (EEM) revealed that the desired positive perceptions of an entrepreneurial business, a stronger tendency to act in an entrepreneurial manner and a possible perceived feasibility to start an entrepreneurial business increase individual tendencies to choose an entrepreneurial career (Urban and Kujinga, 2017). [47] This implies that people are more likely to be involved in entrepreneurship if they consider it interesting and practical -and if they have the capacity to act on identified opportunities (Bacq et al, 2016). [48] Further, another similar study shows that the perceived positive desires of an entrepreneurial business, a stronger tendency to act in an entrepreneurial manner and a positive perception of eligibility to start an entrepreneurial business increase the tendency of individuals to choose an entrepreneurial career (Urban and Kujinga, 2017).…”
Section: Perceived Desirability (Pd)mentioning
confidence: 99%
“…[13] Entrepreneurship education refers to "pedagogical [programs] or any educational process regarding entrepreneurial attitudes and skills" . [14] The aim of entrepreneurship education is to help students increase the likelihood of their business success and to improve careers that they can choose (Nabi et al, 2017). [15] In addition, Schmitz et al, (2017) argue the aim of offering entrepreneurship education at universities is not only to encourage students to start their own businesses but also to make them more creative and innovative.…”
Section: Introductionmentioning
confidence: 99%
“…However, by giving a great importance to a set of innate personality traits, the role of education and training is reduced. Psychological perspective is one of the main areas of entrepreneurship research (Aloulou, 2016). However, due to the neglect of the impact of variables from the environment, empirical research based solely on psychological characteristics is mainly no longer conducted.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the Western Balkans, several research studies on entrepreneurial intentions of students have been carried out (Pfeifer, Šarlija & Zekić Sušac, 2014;Krneta, Alfirević & Đonlagić, 2015;Alfirević, Peronja & Borovac Zekan, 2015;Rajh et al, 2016;Langer, Alfirević, Pavičić & Krneta, 2016;Pašić Mešihović & Šestić, 2016; Baručić & Umihanić, 2016;Petković, 2017;Šestić, Bičo Ćar, Pašić-Mešihović & Softić, 2017), while on a wid er scale, dozens of papers have been published in recent years (Dehkordi, Sasani, Fathi & Khanmohammadi, 2012;Karimi et al, 2015;Mustafa, Hernandez, Mahon & Chee, 2016;Daim, Dabić & Bayraktaroglu, 2016;Aloulou, 2016), which points Students' Career Aspirations towards Entrepreneurial and Managerial Jobs: Saša Petković et al A Comparative Study in Bosnia and Herzegovina, Croatia and Serbia to the importance and relevance of the research topic. Unlike BiH and Croatia, a very little research on entrepreneurial intentions of limited intensity focused on the personal characteristics of respondents was conducted in Serbia (Rajh et al, 2016;.…”
Section: Introductionmentioning
confidence: 99%